A randomized, controlled trial of a web-based tailored intervention to increase human papillomavirus vaccination among people living with HIV/AIDS - Kaliane Caldas de Brito; Miralba Freire de Carvalho Ribeiro da Silva; Cristiane Wanderley Cardoso; Luciano Kalabric Silva; Ricardo Khouri; Antônio Eduardo de Albuquerque Junior; Nelzair Araújo Vianna; Maria da Conceição Chagas de Almeida; Edson Duarte Moreira Junior (PLoS ONE, 2025)
Background Human papillomavirus (HPV) causes several cancers that disproportionally affect people living with HIV/AIDS (PLWH) yet there is a paucity of research on interventions to foster HPV vaccine use in this population. We sought to evaluate the efficacy of a web-based, tailored intervention (e-HPV) to promote HPV vaccination among PLWH. Methods This is a randomized controlled trial with PLWH aged 18 to 45 years. Participants were recruited between January and June 2022 and randomized into two groups: experimental group (e-HPV), which received information about HPV and the HPV vaccine, based on the Protection Motivation Theory and control group, who received a clipping of information from the page maintained by the Ministry of Health dedicated to informing the population about HPV and the HPV vaccine. The primary and secondary outcomes were the percentage of PLWH willing to get HPV vaccine and HPV vaccine initiation (i.e., receipt of any doses by PLWH), respectively. Results A total of 654 individuals were randomly allocated: 327 in the e-HPV and 327 in the control group. The average age was 29.7 years, the majority were men (71.4%), black or mixed race (63.2%). The intention to get vaccinated against HPV was approximately twice as high among participants in the e-HPV vs. control group (OR = 2.0, 95% CI: 1.3–3.4; p < 0.003), and HPV vaccine initiation was also significantly more common among participants in the e-HPV group (OR = 2.1, 95% CI: 1.1-4.0; p = 0.03). Belief in the effectiveness of the HPV vaccine, risk perception and the severity of an HPV infection were the reasons most reported by participants intending to get HPV vaccination. Conclusions The intervention was acceptable and efficacious in increasing HPV vaccination among PLWH. Future studies are warranted to optimize and disseminate the e-HPV intervention to settings providing services to PLWH. Trial registration Brazilian Clinical Trials Registry RBR-557mbvy